1996
DOI: 10.1097/00005537-199609000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Association of Otitis Media With Effusion and Allergy as Demonstrated by Intradermal Skin Testing and Eosinophil Cationic Protein Levels in Both Middle Ear Effusions and Mucosal Biopsies

Abstract: This study was performed to ascertain the role of allergy, as defined by skin testing and histochemical markers, in the pathogenesis of otitis media with effusion (OME). A historical perspective of allergy as it relates to OME is presented. The study included 89 patients: 48 with persistent effusion but no recent acute infection, 25 with purulent OME complicated by a superimposed infection, and 16 control subjects. All 89 patients had persistent effusion for more than 2 months and subsequently required the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
7

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 68 publications
(111 reference statements)
3
38
0
7
Order By: Relevance
“…With progress in basic research on allergies [1] , the middle ear was shown to be an immunoreactive site, both experimentally and clinically [4][5][6] . Recently, Iino et al [7] and Nagamine et al [8] reported OM with eosinophilenriched secretions of which the macroscopic appearance was similar to Koch type OM.…”
mentioning
confidence: 99%
“…With progress in basic research on allergies [1] , the middle ear was shown to be an immunoreactive site, both experimentally and clinically [4][5][6] . Recently, Iino et al [7] and Nagamine et al [8] reported OM with eosinophilenriched secretions of which the macroscopic appearance was similar to Koch type OM.…”
mentioning
confidence: 99%
“…Significant differences between control and patients with OME are indicated by *(p < 0.05), **(p < 0.01), and ***(p < 0.001), respectively; ns = not significant. compared to allergic asthma, and this would again emphasize the multifactorial characteristics of OME [31,32].…”
Section: Discussionmentioning
confidence: 95%
“…In the airways, eosinophilic inflammation has been shown to correlate with the severity of allergic symptoms [23,30]. It has been reported that the majority of patients selected randomly with non-acute OME had elevated levels of ECP in their effusion [31], which suggests a relation between OME, allergy, and eosinophils. Our present findings might lend further support to this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that a reduction in the size of the lumen in an inflamed E-tube could impede mucociliary function, thus delaying clearance of acute infective middle ear effusion, leading to recurrent OME (Alles et al, 2001). Several studies analyzing middle ear mucosa and effusions in atopic patients with OME have demonstrated that the composition of the inflammatory substrate in acute otitis media is similar to the type I late-phase allergic response seen in other areas of the respiratory tract, such as in AR, chronic RS, and asthma (Nguyen et al, 2004;Sobol et al, 2002;Hurst, 1996). The middle ear effusions of atopic patients with OME showed significantly higher levels of eosinophils, T lymphocytes, and IL-4 mRNA+ cells (p<0.01) and significantly lower levels of neutrophils and IFN-γ mRNA+ cells (p<0.01) compared to non-atopic patients with OME (Nguyen et al, 2004).…”
Section: Pathophysiology Of Ome and Armentioning
confidence: 97%